Design and optimization of the readout system for X-ray CCDs - 陆波 崔苇苇 王于仨 朱玥 张艺 徐玉朋 陈勇 霍嘉 李炜 韩大炜 李茂顺 杨彦佶 王娟 陈田祥 胡渭 李承奎 刘晓艳 (Chinese physics C, 2012)
A readout system for X-ray CCDs based on an improved architecture is presented; by optimizing several critical circuit blocks along the analog signal chain, the conflict between the readout speed and readout noise is greatly alleviated. Using CCD47-10 as its target CCD, the readout system has achieved 8.6e^- readout noise and 142 eV FWHM at 5.9 keV Mn Kα under a pixel rate of 80 kHz. Also its performance of imaging has been investigated.